Biomass Yield and Chemical Composition of the Indigenous Browse Species in Gozamen District, Northwestern Ethiopia - Alemu Gashe Desta (International Journal of Forestry Research)
In many regions of Ethiopia, particularly in the study area, high-quality livestock feed is scarce, particularly during the dry season. Indigenous browse species could potentially offer alternative sources of feed, but their potential has not been fully exploited, owing to a lack of detailed information. Without detailed information on the nutritional value of indigenous browse species, it is difficult to assess their suitability as feed sources. This knowledge gap indicates that even if these plants are abundant, they may not be used effectively because their nutritional benefits are not well understood. The objective of the present study was to fill this gap by systematically evaluating the biomass yield and nutritional content of indigenous browse species. The mean biomass yields for various indigenous browse species varied significantly (p<0.05) among species, with Ficus thonningii producing the highest, whereas the biomass yields of Vernonia amygdalina were the lowest. Arundinaria species exhibited the highest NDF content (68.5%), whereas V. amygdalina had the lowest NDF content (46.8%). The crude protein content varied significantly (p<0.05) among the species, with Acacia albida having the highest (20.3%), whereas the crude protein content of Carissa edulis was the lowest (13.3%). Hence, the crude protein content of all indigenous browse species is sufficient to meet the maintenance needs of cattle, sheep, and goats because, as stated by Kearl and NRC, the crude protein levels required for maintenance in these animals range from 7% to 10%. The crude protein content of indigenous browse species is sufficient to meet the milk production requirements of sheep and goats because the crude protein levels required for milk production for these animals range from 12% to 16%. For lactating dairy cows and growing beef cattle, Kearl recommended CP values of 14%–18% and 12%–16% required, respectively. Therefore, indigenous livestock producers should incorporate these species into their production systems to enhance productivity. This approach can also help mitigate the high costs associated with concentrate feeds, which are typically expensive.